Exploring the impact of antenatal micronutrients used as a treatment for maternal depression on infant temperament in the first year of life - Campbell, S. A.; Dys, S. P.; Henderson, J. M. T.; Bradley, H. A.; Rucklidge, J. J. (Frontiers in Nutrition, 2024)
Antenatal depression and maternal nutrition can influence infant temperament. Although broad-spectrum-micronutrients (BSM: vitamins and minerals) given above Recommended Dietary Allowances during pregnancy can mitigate symptoms of antenatal depression, their associated effects on infant temperament are unknown. One hundred and fourteen New Zealand mother-infant dyads (45 infants exposed to BSM during pregnancy (range of exposure during pregnancy: 12–182 days) to treat antenatal depressive symptoms (measured by Edinburgh Postnatal Depression Scale) and 69 non-exposed infants) were followed antenatally and for 12 months postpartum to determine the influence of in utero BSM exposure on infant temperament. The Infant Behavior Questionnaire–Revised: Very Short-Form assessed temperament at 4 (T1), 6 (T2) and 12 (T3) months postpartum via online questionnaire. Latent growth curve modelling showed BSM exposure, antenatal depression and infant sex did not statistically significantly predict initial levels or longitudinal changes in orienting/regulatory capacity (ORC), positive affectivity/surgency (PAS) or negative affectivity (NEG). Higher gestational age was positively associated with initial PAS, and smaller increases between T1 and T3. Breastfeeding occurrence was positively associated with initial NEG. Although not significant, BSM exposure exerted small, positive effects on initial NEG (β = -.116) and longitudinal changes in ORC (β = .266) and NEG (β = -.235). While BSM exposure did not significantly predict infant temperament, it may mitigate risks associated with antenatal depression. BSM-exposed infants displayed temperamental characteristics on par with typical pregnancies, supporting the safety of BSM treatment for antenatal depression.